A importância do Cirurgião Dentista do serviço público e privado na identificação e no processo de notificação de violência - Alves, Tamyres Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Violence is, nowadays, a daily struggle for some people. For others, it's just an act covered by the mass media or a scene witnessed in day-to-day environments. Maltreatment affects a population that has no means to defend itself and such category includes the children, the elderly and the women, who are at the mercy of violence without proper defense capability. The reports of incidence of attacks have become increasingly frequent in several countries, even in those that are considered to be developed. Nevertheless, what many health professionals do not know, especially the surgeon dentists, is that violence can be combated through its notification and complaint. As if that was not enough, dentists are unaware of the fact that they are the ones that have most contact with the injuries coming from the aggressions, since these are, most of the times, in the head and neck. Through a bibliographical research, this study aims to examine the role of these professionals in this kind of situation, which can often go unnoticed by them. Furthermore, this study has the intention to show the legal duty of this professional whenever there is a suspicion or confirmation of maltreatment, when it comes to patients who have increased vulnerability. Researches show that most of surgeon dentists reported that they received no training in relation to domestic violence issues when they were students and that they do not feel prepared to deal with situations surrounding this issue. it was also noted that, in accordance with the articles, that when these professionals suspected that some of their patients suffered maltreatment, they could even express a complaint or a notification, but did not know to whom or to which administrative body they must appeal and neither about their legal responsibility in face of such fact. The conclusion...

A violência atualmente é uma luta diária para alguns. Para outros, é apenas uma notícia em um meio de comunicação ou então uma cena presenciada em ambientes rotineiros. Os maus-tratos atingem uma população que não possui meios de se defender e estão nesta categoria as crianças, os idosos e as mulheres, que ficam à mercê da violência, sem capacidade de defesa. Há relatos da incidência de agressões cada vez mais frequentes em diversos países, até naqueles que são considerados desenvolvidos. Porém, o que muitos profissionais da saúde não sabem, em especial o cirurgião-dentista, é que a violência pode ser combatida através da sua notificação e denúncia. Ainda, desconhecem o fato de que ele é o que mais tem contato com as lesões provenientes das agressões, uma vez que estas se encontram, em sua maior parte, na região de cabeça e pescoço. Por meio de uma pesquisa bibliográfica, esse trabalho tem como objetivo analisar o papel desses profissionais frente a esse tipo de situação, a qual muitas vezes pode passar despercebida pelo mesmo. Além disso, tem como intuito mostrar o dever legal desse profissional quando houver uma suspeita ou confirmação de maus-tratos quando se trata de pacientes que possuem maior vulnerabilidade. Pesquisas mostram que a maioria dos cirurgiões-dentistas relatou que não receberam nenhum preparo em relação ao assunto violência doméstica quando discentes, e que não se sentem preparados para lidar com situações que envolvam o tema. Observou-se também, de acordo com os artigos, que esses profissionais, quando suspeitaram que alguns de seus pacientes sofriam maus-tratos, até fariam a denúncia ou notificação, porém não sabiam a quem ou a qual órgão recorrer, e nem da sua responsabilidade legal diante de tal fato. Conclui-se que apesar do cirurgião-dentista ter a obrigação de zelar...
Keywords: Violência; Odontólogos; Criança; Idosos; Mulheres; Violence